2018
DOI: 10.1111/jgh.13903
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal fat as a non‐invasive marker of increased risk of severe non‐alcoholic fatty liver disease in patients with type 2 diabetes

Abstract: Visceral fat area was the best predictor of fibrosis in patients with type 2 diabetes. Preperitoneal fat area was the best predictor of steatohepatitis and is a potential new non-invasive marker for use in the screening of these patients to detect more aggressive forms of non-alcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…Conversely, Parente et al concluded that there was no correlation between the subcutaneous fat thickness and the grade of steatosis among type 2 diabetic obese individuals,25 and this result is in accordance with other previous studies which suggested that visceral fat, not subcutaneous fat, is a reliable predictor of NAFLD 26,27…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, Parente et al concluded that there was no correlation between the subcutaneous fat thickness and the grade of steatosis among type 2 diabetic obese individuals,25 and this result is in accordance with other previous studies which suggested that visceral fat, not subcutaneous fat, is a reliable predictor of NAFLD 26,27…”
Section: Discussionsupporting
confidence: 78%
“…For cT1 as well, an optimal cut‐off (875 ms) has been suggested, but to distinguish between low‐ and high‐risk (NASH or fibrosis > 1) patients, with sensitivity/specificity of 97%/50%. Other MRI approaches include quantitative susceptibility imaging, intravoxel incoherent motion (IVIM) diffusion‐weighted MRI, and morphological evaluation such as liver volume and preperitoneal fat area, all evaluated in one single study, with AUROCs ranging from 0.61/0.68/0.74 for different IVIM parameters to 0.91 for susceptibility, the last one tested in a small sample of 32 patients. Moreover, a score based on MRI optical analysis estimators produced an AUROC of 0.83 with sensitivity/specificity of 87%/60% .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, US scores mostly evaluating liver hyperechogenicity present high referral rates and low positive predictive values to obtain high sensitivity. Preperitoneal fat area and perihepatic adipose tissue thickness, evaluated by means of MRI and US, likewise showed high sensitivities and relatively low specificities at the proposed thresholds. Indeed, these are not direct measures of inflammation but rather indicators of visceral adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with VAT and SAT, adipose-derived stem/stromal cells derived from pPAT revealed highest capacity to generate new adipocytes by adipogenesis and low proinflammatory profile ( 61 ). Nevertheless, pPAT behaves like VAT and is correlated positively with hypertension, dyslipidemia, insulin resistance, cardiovascular disease risks, and obesity ( 5 , 31 ). Compared with previous research, we found that pPAT area was significantly associated with hypertension, T2DM, high TG, low-HDL-C, CCRFs, and measures of TG and HDL-C independent of BMI in men rather than women.…”
Section: Discussionmentioning
confidence: 99%
“…pPAT was defined as the fat depot anteriorly seen from the anterior surface of the left lobe of the liver to the linea alba ( 31 ). pPAT area and FF were measured using the spline contour region of interest (ROI) method ( Figure 1D ).…”
Section: Methodsmentioning
confidence: 99%